Amazonia and the idea of Infinite of Emmanuel Levinas: paths and possibilities - Pascoal, Rosana Moraes (2020)
The objective of this article is to address the idea of Infinite by the philosopher Emmanuel Levinas, as an epistemological possibility to look at the Amazon outside the dominant western view that the region was submitted to during its colonization process. Methodologically, the study took place through bibliographic research, with a qualitative approach. The main results show that the idea of Infinite opens ways to think beyond the totalizing and dominating views of the world, thus allowing analyzes that make it possible to understand the complexity and socio-cultural wealth of the Amazon region, where its subjects can be seen as protagonists of their stories.